2015
DOI: 10.1175/jas-d-14-0249.1
|View full text |Cite
|
Sign up to set email alerts
|

Column-Integrated Moist Static Energy Budget Analysis on Various Time Scales during TOGA COARE

Abstract: Moist static energy (MSE) budgets on different time scales are analyzed in the TOGA COARE data using Lanczos filters to separate variability with different frequencies. Four different time scales (;2-day, ;5-day, ;10-day, and MJO time scales) are chosen based on the power spectrum of the precipitation and previous TOGA COARE studies. The lag regression-slope technique is utilized to depict characteristic patterns of the variability associated with the MSE budgets on the different time scales.This analysis illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
73
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 72 publications
13
73
1
Order By: Relevance
“…In both MJO events, time‐independent radiation causes increased precipitation before or at the start of the active phase (e.g., the first 10 days, days 36, 40, and 60) and decreased precipitation in the peaks of the active phases by 30–50%, compared to that obtained with specified time‐dependent radiation. Consistent with much previous work [e.g., Lin and Mapes , ; Bony and Emanuel , ; Kim et al ., ; Sobel and Maloney , ; Inoue and Back , ; Creuger and Stevens , ], this evidence suggests that time‐dependent radiative heating anomalies associated with MJO convection are a significant source of moist static energy during the MJO active phase.…”
Section: Resultsmentioning
confidence: 93%
“…In both MJO events, time‐independent radiation causes increased precipitation before or at the start of the active phase (e.g., the first 10 days, days 36, 40, and 60) and decreased precipitation in the peaks of the active phases by 30–50%, compared to that obtained with specified time‐dependent radiation. Consistent with much previous work [e.g., Lin and Mapes , ; Bony and Emanuel , ; Kim et al ., ; Sobel and Maloney , ; Inoue and Back , ; Creuger and Stevens , ], this evidence suggests that time‐dependent radiative heating anomalies associated with MJO convection are a significant source of moist static energy during the MJO active phase.…”
Section: Resultsmentioning
confidence: 93%
“…Their definition of NGMS is the ratio between the anomaly of column-integrated vertical advection of MSE to that of DSE. Testing this assumption is complicated by the difficulty of precisely estimating NGMS from observations; however, several modeling and observational studies indicate that NGMS significantly varies with the MJO phase (Benedict et al 2014;SWK;Wang et al 2015;Inoue and Back 2015). SWK found that NGMS increases as the MJO convective active phase passes.…”
Section: Impact Of Assumptions For Simplificationmentioning
confidence: 99%
“…The Tropical Ocean Global Atmosphere program Coupled Ocean-Atmosphere Response Experiment (TOGA COARE; Webster and Lukas 1992) conducted a field campaign over the equatorial western Pacific in 1992/93 austral summer, and the Cooperative Indian Ocean Experiment on Intraseasonal Variability in the Year 2011 (CINDY2011)/Dynamics of the MJO (DYNAMO) project conducted a field campaign focusing on central Indian Ocean in 2011/12 austral summer (Yoneyama et al 2013). While there have been a number of studies performing budget analyses of dry static energy (DSE) and moisture using data obtained during these campaigns (Lin and Johnson 1996a, b;Ciesielski 2000, 2013;Johnson et al 2015, and others), only a few studies have focused on MSE budget Inoue and Back 2015). Sobel et al (2014, hereafter SWK) examined the column-integrated MSE budget over the Indian Ocean using datasets collected by the CINDY2011/DYNAMO project together with complementary data.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the horizontal advection of MSE depends on horizontal moisture gradient in the large-scale environment and could irregularly modulate the thermodynamic variability that otherwise would be controlled by internal convective dynamics. While horizontal advection could play crucial roles in the driving mechanism of the MJO (e.g., Benedict and Randall 2007;Maloney 2009;Sobel et al 2014), the relative magnitude of hori- zontal and vertical advections is dependent on the cycle of variability and the horizontal component is least important at daily time scales (Inoue and Back 2015). Figure 13 shows the breakdown of moisture/MSE convergence into horizontal and vertical advections calculated from the ensemble mean of all CINDY/DYNAMO events.…”
Section: Discussionmentioning
confidence: 99%